Uterine leiomyosarcoma with atypical metastasis post total hysterectomy: Case report - Quispe-Vicuña, Carlos (2023)
Introduction: Uterine leiomyosarcoma is a rare and highly aggressive sarcoma, which can metastasize most frequently to the lung and liver. Its prognosis is poor, with early total abdominal hysterectomy being the first line treatment. Other alternatives are chemotherapy with regimens of doxorubicin, ifosfamide or gemcitabine, alone or in combination. Case report: We present a 40-year-old Peruvian woman who underwent hysterectomy for suspected leiomyoma; however, pathology revealed a final diagnosis of uterine leiomyosarcoma. She could not be notified due to loss to follow-up. Two years later, she again presented with metastases in the thigh, breast, liver, lungs and scalp. He was given Ifosfamide and Doxorubicin every 21 days for 3 courses, however, due to disease progression, palliative treatment was decided. Finally, he died two months after treatment. Conclusion: A case of uterine leiomyosarcoma with atypical metastasis is presented to promote early and differentiated diagnosis of leiomyoma, low grade leiomyosarcoma and high grade leiomyosarcoma to define the correct treatment.